The Use of Fractional Manipulative Media to Increase The Conceptual Understanding of Elementary School Students - Rostien Puput Anggoro (Universitas Tidar, 2019)
Learning mathematics at the elementary school level is very important in planting basic concepts about the concepts being taught. One effective way of learning mathematics in planting these concepts is by using manipulative media. Based on the results of observations of researchers in class II C of Muhammadiyah Elementary School, Nitikan, Yogyakarta obtained: 1) mathematics learning rarely uses the media, 2) the subject of fractions is difficult material with marked results of the pretest only 53.1% who reach minimum completeness criterion. This study aims to describe learning using manipulative media to improve understanding of the subject matter of fractions. This study uses a Classroom Action Research (CAR) design. The subjects of this study are class II C of Muhammadiyah Elementary School, Nitikan, amounting to 32 students. Data collection techniques used are observation and test. Data analysis in this classroom action research is quantitative and qualitative data analysis. The results showed the ability to understand the concept of mathematics in the first cycle is 62,5 % with good criteria and the second cycle is 78.1 % with good criteria. The results of observations of the feasibility of using manipulative media in learning mathematics on the subject matter of fractions seen based on the activities of teachers and students during the learning process. Based on research that has been done, it can be concluded that the ability to understand mathematical concepts and student learning activities in class II C of SD Muhammadiyah Nitikan increases after the application of learning using manipulative media.